Strength and Conditioning Practices and Perspectives of Volleyball Coaches and Players - Anthony Weldon; Jason T. S. Mak; Sing T. Wong; Michael J. Duncan; Neil D. Clarke; Chris Bishop (MDPI AG, 2021)
To the authors' knowledge this is the first study to describe the strength and conditioning (S&C) practices and perspectives of volleyball coaches and players. In total, 30 volleyball coaches (mean age 34.47 ± 7.83 years and coaching experience 19.57 ± 8.28 years), and 30 volleyball players (mean age 22.03 ± 4.43 years and playing experience 10.43 ± 8.98 years) completed an online survey with six sections: (a) informed consent; (b) background information; (c) education, qualifications, and prescription; (d) views on S&C; (e) exercise selection and preferences; and (f) issues and improvements. Frequency analysis was used to report responses to fixed-response questions and thematic-analysis for open-ended questions. While only one participant possessed an S&C certification, S&C was deemed 'important' to 'very important' for volleyball skills, physical fitness, and injury parameters. However, due to a reported lack of expertise, there appeared to be a theoretical understanding to practice gap. Furthermore, the implementation of S&C was considerably hindered by a lack of time, facilities, and equipment. National sports associations, coaches, and players can use the information within this study to provide an understanding of the current practices and perspectives of S&C in volleyball. While also promoting future developments in volleyball related S&C research and practice.